How and why policy-practice gaps come about: a South African Universal Health Coverage context - Janet Michel; Natsayi Chimbindi; Nthabiseng Mohlakoana; Marsha Orgill; Till Bärnighausen; Brigit Obrist; Fabrizio Tediosi; David Evans; Di McIntryre; Hans T Bressers; Marcel Tanner (Journal of Global Health Reports)
# Background